(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Pediatric radiology nursing demands a tailored approach to address the distinct needs of young patients undergoing radiologic procedures. This article delineates special considerations and best practices imperative for optimal pediatric care within radiology settings. Key considerations encompass age-appropriate communication, fostering a child-friendly environment, anxiety mitigation strategies, and meticulous safety precautions. Best practices underscore the significance of collaborative teamwork, empathetic engagement, continuous education, and unwavering advocacy for pediatric patients. By adhering to these principles, radiology nurses can ensure the delivery of safe, compassionate, and effective care, thereby enhancing the overall experience for pediatric patients and their families.